Organic production - A strategic decision determining the agricultural income of small farms in Poland - Siemaszkiewicz, Paweł (Humanities & Social Sciences Reviews, 2023)
Research objective: The main objective of the work was to determine the change in agricultural income after the implementation of organic production by small farms and to indicate the impact of organic production on the development of the farm, e.g. in the investment area. Methodology: The study covered a group of 132 small farms engaged in organic production. The primary material was obtained using the survey method using a questionnaire. The study covered farms whose area did not exceed 10 hectares, where organic production was carried out and operated on the territory of the Republic of Poland. Main conclusions: the implementation of organic production positively affects the agricultural income obtained by a small farm. It causes its growth and also favors making investments by the entity. Agricultural income is one of the basic factors motivating investment in farms. It guarantees a sense of economic security for the farmer and his family and affects the development of the farm. Application of the study: The findings of this study can be instrumental for policymakers, agricultural organizations, and farmers in the Republic of Poland. By understanding the positive economic implications of organic production for small farms, stakeholders can make informed decisions about promoting and adopting organic farming practices. Additionally, financial institutions might consider these findings when offering financial products or incentives tailored for organic farmers. Originality/Novelty of the study: This research stands out as one of the few comprehensive studies focusing on the economic implications of organic production specifically for small farms in the Republic of Poland. While there have been studies on organic farming, the emphasis on small farms, which often face distinct challenges and opportunities, brings a fresh perspective to the discourse.